Contributing Factors of Time Overrun in Public Sector Construction Projects - Akhund, M. A.; Imad, H. U.; Memon, N. A.; Siddiqui, F.; Khoso, A. R.; Panhwar, A. A. (Engineering, Technology & Applied Science Research, 2018)
Time overrun is a major issue in construction projects. Its causes vary, depending upon the nature and size of the project. Developing countries are more susceptible to this problem due to limited resources and lack of managerial skills. This paper focuses on the identification and classification of time overrun factors in public sector projects in Pakistan. Data was collected by the use of a questionnaire given to different professionals in the construction field. Average index (AI) was used to determine each factor’s relative importance. Results indicate that financial difficulties faced by constructor, inadequate planning and scheduling, financial difficulties faced by client, delays in payment by the client, delays in decision making by the client, design mistakes, frequent design changes, material shortage, incompetent sub-constructor assigned by the constructor, poor site management and supervision and inadequate constructor’s experience are the most significant factors of time overrun in public sector construction projects in Pakistan. This study aims to be useful in addressing the issue of time overrun in the construction industry.